The nature and extent of environmental sustainability advertising in magazines in a developing market. (6th May 2022) - Ndlovu, Sibusiso; Ellis, Debbie
Consumers' unsustainable consumption patterns play a substantial role in environmental deterioration. For consumers to behave more sustainably, they need to be knowledgeable of the problems, and various product and service solutions. Some businesses are using environmental sustainability advertising to develop consumer awareness and to influence environmentally conscious behaviour. This paper investigated the extent and nature of environmental sustainability advertising in magazines in a developing nation. A descriptive design with a deductive content analysis of 66 magazines revealed a limited number of environmental sustainability advertisements which are described in terms of their structure and content. This research contributes to marketers using environmental sustainability messages, conceptualising the types of message elements currently being used in magazine advertising and possible alternatives for making the environmental sustainability message unique. Recommendations are made for environmental sustainability marketers, academics, policymakers and future research.